2-Ketoisocaproate transport in insulin-secreting cells. Issue 1 (February 1992) - Best, L.; Trebilcock, R.; Tomlinson, S.
Abstract : The transport of the nutrient secretagogue 2-ketoisocaproate (KIC) was studied in isolated rat pancreatic islets and in the HIT-T15 insulinoma cell line using an oil-filtration technique. In both islets and HIT-T15 cells, KIC uptake was a slow process, not reaching equilibrium within 10 min KIC transport was not dependent upon Na + in the medium, was not inhibited by α-cyano-4-hydroxy-cinnamate nor by 2-amino-2-norborane carboxylic acid (BCH) and did not appear to be electrogenic. Evidence was obtained to suggest that KIC uptake occurred via passive diffusion into the cell of the undissociated acid species. This possibility was supported by the apparent unsaturability of KIC uptake in HIT-T15 cells. Addition of 10–30 mM KIC to dispersed islets cells or HIT-T15 cells produced a rapid intracellular acidification. In islets, the rate of transport of 10 mM KIC was comparable with oxidation rate of the keto-acid suggesting that uptake could be rate-limiting factor for KIC oxidation and thus stimulated insulin release. However, in HIT-T15 cells, the rate of uptake of KIC greatly exceeded the oxidation rate. The low rate of KIC oxidation could explain the poor secretory response of HIT-T15 cells to KIC